Biomass and nutrients of accumulated litter in different forest covers - Caldeira, Marcos Vinicius Winckler; Silva, Robertino Domingues da; Kunz, Sustanis Horn; Zorzanelli, João Paulo Fernandes; Castro, Kallil Chaves; Godinho, Tiago de Oliveira (Comunicata Scientiae, 2013)
This study aimed to assess biomass and nutrients from the litter in a conservation area in the municipality of Alegre, ES. The study was conducted in three different forest covers included in the Area of Ecological Interest (ARIE) Laerth Paiva Gama, being a Native Forest (MN), a Reforestation of Eucalyptus and Acacia (REA) and Reforestation of several species (RED). The litter layer was measured by the amount of biomass, the content and accumulation of nutrients in both harvests, the first in the late dry season and the second end of the rainy season. In all the coatings, the quantity of biomass was greater in the dry and followed values decreasing the amount of biomass in both forest cover: REA > RED> MN. The levels of potassium, magnesium and boron, present in the litter were higher in the dry season, however the levels of nitrogen, phosphorus, calcium, sulfur, copper, iron, manganese and zinc, and organic carbon content did not differ between periods of collection, only being discrepant between forest cover, no seasonal variation. The type of forest cover has little influence on the levels of nutrients and in the dry season the accumulation of litter, potassium, magnesium and boron were also indifferent to this variable.